Sosialisasi Tumbuhan Nelambo Suon (Rubiaceae) Sebagai Pencegah Penyakit Malaria Berdasarkan Kearifan lokal Pada Masyarakat Distrik Walma dan Heriapini, Yahukimo - Nelambo, Tomi A.; Suharno, Suharno (Bakti Hayati: Jurnal Pengabdian Indonesia, 2024)
Nelambo Suon (Rubiaceae) is one of the traditional antimalarial medicinal plants used by people in Walma and Heriapini Districts, Yahukimo. This plant lives on cliffs and grows wild in home yards to tropical rainforests. The purpose of this activity is to provide education to the community about how to use the Nelambo Suon plant as a prevention of malaria. The activity was carried out in Perumnas 4 Waena, Jayapura City to people from Walma and Heriapini districts who were studying further. The method of this activity is Focus Group Discussion (FGD) and training in making medicinal herbs to prevent and treat malaria. Activities were carried out in August-October 2022, which were carried out well and smoothly. The results of the activity showed that there was an increase in understanding in the utilization of Nelambo Suon plants up to an average of 78.57% (74.44% to 94.74%). This increase is expected to be able to maintain the understanding and motivation of the community to continue to pay attention and utilize the Nelambo Suon plant as a traditional medicine to prevent and cure malaria.